Development of telecommunications sector in Cambodia, Laos, Myanmar and Vietnam and Impacts on economic growth: An analysis with pooled mean group estimator - Pyae Phyo May (2018)
© Serials Publications Pvt. Ltd. Telecommunications is regarded as an essential infrastructure for national economic development and competitiveness. In developing countries, telecommunications development can be a means to achieve economic growth. This study reviews the development of telecommunications sector and examines its impacts on economic growth in the CLMV countries (Cambodia, Laos, Myanmar, and Vietnam) over the period of 2000 to 2015 using the pooled mean group estimator (PMGE). The results show thatfixed line telephony subscription, mobile phone subscription and internet users have positive correlations with economic growth in the CLMV countries. In addition, the telecommunications sector is different for each ASEAN country, and it must correspond to each social, political and economic needs.As a region, ASEAN trends towards different forms of deregulation, liberalization of markets and privatization of the telecommunications authorities. The result provides a guideline to implement reforms in the ICT sector and economic development of CLMV countries. This study concludes that telecommunications are a key driver of CLMV economic growth.